From Bureaucracy to Efficiency: The Impact of Licensing Service Quality on Increasing Regional Investment: A Case Study at the Pekanbaru Public Service Mall (Jurnal Bina Praja, 2025)
This study aims to analyze the effect of the quality of licensing services on increasing regional investment in the Public Service Mall (MPP) of Pekanbaru City. The study used mixed methods of the Explanatory Sequential method. Researchers distributed questionnaires to 384 respondents who used the Business Identification Number (NIB) service, followed by interviews with several business actors regarding their interest in investing, seen from the quality of licensing services in Pekanbaru City. Quantitative data were analyzed through validity and reliability tests, linear regression, and t-tests, resulting in a significant positive effect with a correlation coefficient (R) of 0.955 and a determination (R²) of 91.1%. Qualitative findings confirm that users positively assess tangibles, reliability, responsiveness, assurance, and empathy. The qualitative approach also reveals that the integration of the OSS and regional innovations improves access to investment facilities. These results indicate that improvements in licensing services directly encourage investment realization, creating a more conducive and competitive regional investment climate.
Keywords: Quality of Licensing Services; Regional Investment; Public Service Mall; Public Service Efficiency; Pekanbaru City